Advances in dependability engineering of complex systems : proceedings of the twelfth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, July 2-6, 2017, Brunów, Poland /: proceedings of the twelfth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, July 2-6, 2017, Brunów, Poland. (2018) - Unknown
No abstract available